The Interplay of Aging and PANoptosis in Osteoarthritis Pathogenesis: Implications for Novel Therapeutic Strategies - Liu S; Zhang G; Li N; Wang Z; Lu L (Journal of Inflammation Research)
Shaoshan Liu,1,* Guifeng Zhang,2,* Nan Li,3 Zheng Wang,4 Liaodong Lu1 1Department of Joint Surgery, Liaocheng Traditional Chinese Medicine Hospital, Liaocheng, 252000, People’s Republic of China; 2Department of Neurology, Liaocheng People’s Hospital and Liaocheng Hospital Affiliated to Shandong First Medical University, Liaocheng, 252000, People’s Republic of China; 3Department of Trauma Orthopedics, Liaocheng Traditional Chinese Medicine Hospital, Liaocheng, 252000, People’s Republic of China; 4Department of Neurosurgery, Liaocheng Traditional Chinese Medicine Hospital, Liaocheng, 252000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zheng Wang, Email zhengyimingdao@gmail.com; Liaodong Lu, Email shuier_226@163.comAbstract: Osteoarthritis (OA) is a common degenerative joint disease characterized by the progressive degradation of articular cartilage, synovial inflammation, and subchondral bone remodeling. This review explores the interplay between aging, PANoptosis, and inflammation in OA progression. Age-related cellular and immune dysfunctions, including cellular senescence, senescence-associated secretory phenotypes (SASPs), and immunosenescence, significantly contribute to joint degeneration. In OA, dysregulated apoptosis, necroptosis, and pyroptosis, particularly in chondrocytes, exacerbate cartilage damage. Apoptosis, mediated by the JNK pathway, reduces chondrocyte density, while necroptosis and pyroptosis, involving RIPK-1/RIPK-3 and the NLRP3 inflammasome, respectively, amplify inflammation and cartilage destruction. Inflammatory cytokines and damage-associated molecular patterns (DAMPs) further enhance these PANoptotic pathways. Current therapeutic strategies primarily focus on anti-inflammatory agents such as non-steroidal anti-inflammatory drugs (NSAIDs) and corticosteroids, with growing interest in anti-senescence drugs targeting cellular senescence and SASP. Additionally, exploring PANoptosis mechanisms offers potential for innovative OA treatments.Keywords: osteoarthritis, aging, senescence, PANoptosis, inflammation, therapeutic strategies